Sifat pemurah dan menjauhi sifat kikir - Rahmatullah, Agung; haqqy, ahmad jauhari (Maliki Interdisciplinary Journal, 2025)
Generosity and avoiding stinginess are two crucial traits in social and spiritual life. Generosity reflects a person's concern and empathy for others, which can strengthen social relationships and create a more comfortable environment. Conversely, stinginess can spread negative influences in society, diminishing a sense of family, and increasing social inequality. From a religious and moral perspective, generosity is often associated with blessings and happiness, while stinginess can have negative impacts on both the individual and their surroundings. Therefore, efforts to cultivate generosity and suppress stinginess need to be integrated into moral, social, and character development to develop individuals with noble character, who care for others, and are able to contribute positively to the welfare of society.